Multi-objective optimization of a multiphase pump booster unit for enhanced hydraulic performance - Dong, Pingyang; Shi, Guangtai; Xiao, Yexiang; Wen, Haigang; Lv, Wenjuan; Peng, Xiaodong (Frontiers in Mechanical Engineering, 2026)
As key equipment in oil and gas transmission systems, multiphase pumps are crucial for ensuring a closed oilfield collection and transmission. The booster unit as the core component of the multiphase pump, has blade shapes that significantly impact the pump efficiency and its gas-liquid mixing performance. To enhance the efficiency of the booster unit and improve its gas-liquid mixing, this study first employed an optimal Latin hypercube design to sample blade shape parameters and establish a design library. The effects of these parameters were systematically investigated via numerical simulation. Subsequently, an approximate prediction model was developed and integrated into a multi-objective optimization framework to identify Pareto-optimal blade configurations. Following optimization, the pump efficiency increased from 52.60% to 54.56% (a 3.59% improvement), while the gas uniformity at the impeller outlet decreased from 0.3229 to 0.3040 (a 6.22% reduction). Comparative analysis of internal and external characteristics confirmed improved gas dispersion and more refined flow field structures within the optimized booster unit. The proposed methodology integrates advanced sampling, modeling, and optimization techniques, providing a systematic and efficient strategy for the performance-driven design of multiphase pump blades. This framework offers significant potential for enhancing the hydraulic performance and operational stability of such critical transport equipment.